Post-exercise hypotension: possible relationship with ethnic and genetic factors. DOI: http://dx.doi.org/10.5007/1980-0037.2012v14n3p353 - Emerson Pardono; Afrânio Andrade Bastos; Marcos Bezerra Almeida; Herbert Gustavo Simões (Universidade Federal de Santa Catarina, 2012)
Post-exercise hypotension (PEH) is characterized by a decrease in blood pressure (BP) in relation to pre-exercise levels and has been intensively studied in different populations after different modes of exercise. Several mechanisms are associated with PEH, which makes it a multifactorial condition. However, over the last decade, some studies aimed to investigate the possible influence of ethnic and genetic factors on PEH. Thus, the purpose of this study was to review the environmental and, mainly, ethnic and genetic factors related to PEH. The studies used herein were obtained from a review of the following online databases: MEDLINE, SciELO and, Portal Capes. In relation to ethnicity, studies appear to indicate an unfavorable trend toward development of PEH in blacks as compared to whites, although this cannot be stated categorically. As for genetic studies and PEH, we stress the importance of these studies and highlight the need for selecting candidate genes for research on the basis of the physiological system implicated in BP regulation. Published studies have basically examined the relationship between PEH and mutations in genes that express proteins involved in the renin-angiotensin-aldosterone system. In this genetic sense, it seems that the greatest decline in PA occurs mainly after low-intensity aerobic exercise performed by normotensive or borderline hypertensive adult men. Further studies on the subject are required.